1988
DOI: 10.1021/j100318a047
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of water-in-oil droplets stabilized by sodium bis(2-ethylhexyl)sulfosuccinate

Abstract: The structure and dynamical behavior of water-in-oil microemulsions, stabilized by sodium bis(2-ethylhexyl) sulfosuccinate (AOT), has been studied by means of time-resolved fluorescence probing. The surfactant aggregation number, N, and the second-order rate constant, ke, associated with the intermicellar exchange of reactants by collision and transient merging of the colliding micelles, increase as the temperature, the chain length of the oil used as solvent, the molar concentration ratio = [H20]/[AOT], and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
207
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(232 citation statements)
references
References 13 publications
23
207
1
1
Order By: Relevance
“…The data in Table 2 show an increase of the quenching rate constant with temperature, as previously reported for similar systems (12,20).…”
Section: Figsupporting
confidence: 85%
See 2 more Smart Citations
“…The data in Table 2 show an increase of the quenching rate constant with temperature, as previously reported for similar systems (12,20).…”
Section: Figsupporting
confidence: 85%
“…Lang et al (20) have also reported a small dependence of N on temperature in the range 15-35°C for the AOT/C 7 /W microemulsion. Large increases of N with T are observed with microemulsions only at the approach of a percolation threshold (20,21). All of the systems selected for the present investigation are not in this situation.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The list includes fluorescence, 3,4 NMR, [5][6][7] neutron and x-ray scattering, [8][9][10][11] quasi-elastic light scattering, and infrared 12,13 and terahertz 14 spectroscopies, to cite a few relevant examples. On the other hand, and from a theoretical perspective, these systems have also been investigated, normally resorting on computer simulations incorporating different degrees of molecular detail to model the polar and non-polar phases and the surfactants as well.…”
Section: Introductionmentioning
confidence: 99%
“…There%re the activation parameters should be treated as apparent ones. The apparent activation energies of intermicellar exchange in AOT reverse micelles in n-heptane, i-octane and decane estimated from the kinetic data published by Lang et al [6] are 94, 88 and 66 kJ/mole, respectively. It means that they decrease with increasing viscosity of the solvent.…”
Section: Probing Igepal Reverse Nlicelles With a Solvated Electronmentioning
confidence: 91%